2022
DOI: 10.1002/brb3.2779
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam versus Oxcarbazepine as monotherapy in newly diagnosed focal epilepsy: A systematic review and meta‐analysis

Abstract: Objective: To compare the efficacy and safety of Levetiracetam (LEV) and Oxcarbazepine (OXC) as monotherapy for the treatment of newly diagnosed focal epilepsy. Methods:We searched PubMed, Cochrane Library, EMBASE, and Google Scholar from January 1, 2000 to May 11, 2022, with no language restrictions along with The Clini-calTrials.gov website and the WHO International Controlled Trials Registry platforms.We pooled the risk ratio (RR) and corresponding 95% confidence interval (95% CI) for the efficacy and safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(46 reference statements)
0
4
0
1
Order By: Relevance
“…Specifically, LEV is a relatively new second-generation AEDs, and it can bind selectively to proteins related to neurotransmitter release, which can work rapidly. 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, LEV is a relatively new second-generation AEDs, and it can bind selectively to proteins related to neurotransmitter release, which can work rapidly. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, LEV is a relatively new second-generation AEDs, and it can bind selectively to proteins related to neurotransmitter release, which can work rapidly. 12 Moreover, OXC is a new-generation AEDs derived from traditional AEDs, with few side effects. It plays an anti-convulsive role mainly by blocking sodium channel and promoting potassium conduction, and has a good therapeutic effect on children.…”
Section: Discussionmentioning
confidence: 99%
“…OXC is not recommended for elderly patients with a history of cardiac conduction abnormalities or ventricular arrhythmias ( 63 ). A meta-analysis of LEV and OXC as monotherapy showed that their adverse effects did not differ much, but LEV had better seizure control ( 64 ). A study showed that epileptic patients who took carboxamide derivatives (including OXC) had a higher risk of arrhythmia than epileptic patients without medication and those without epilepsy ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind this may lie in the fact that oxcarbazepine, as a second-generation antiepileptic drug, possesses favorable pharmacokinetics. It can block voltage-dependent calcium or sodium ion channels, inhibit hyperexcitability of neuronal membranes, reduce synaptic activity, stabilize emotions, and alleviate anxiety and depression [24,25].…”
Section: Discussionmentioning
confidence: 99%